2007
DOI: 10.1007/s00125-007-0778-x
|View full text |Cite
|
Sign up to set email alerts
|

GLUT2 protein at the rat proximal tubule brush border membrane correlates with protein kinase C (PKC)-βl and plasma glucose concentration

Abstract: Aims/hypothesis GLUT2 is the main renal glucose transporter upregulated by hyperglycaemia, when it becomes detectable at the brush border membrane (BBM). Since glucoseinduced protein kinase C (PKC) activation in the kidney is linked to diabetic nephropathy, we investigated the effect of glycaemic status on the protein levels of PKC isoforms α, βI, βII, δ and ɛ in the proximal tubule, as well as the relationship between them and changes in GLUT2 production at the BBM. Methods Plasma glucose concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…2A). As previously demonstrated (Marks et al 2003;Goestemeyer et al 2007), exposure to streptozotocin induced hyperglycaemia (Table 1). Interestingly, while GLUT2 and PKC-βI expression at the BBM was significantly increased, SGLT1 and SGLT2 levels were unaffected 1-week after streptozotocin injection (Fig.…”
Section: Type II Diabetes Increases Sglt-and Glut-mediated Transport supporting
confidence: 55%
See 2 more Smart Citations
“…2A). As previously demonstrated (Marks et al 2003;Goestemeyer et al 2007), exposure to streptozotocin induced hyperglycaemia (Table 1). Interestingly, while GLUT2 and PKC-βI expression at the BBM was significantly increased, SGLT1 and SGLT2 levels were unaffected 1-week after streptozotocin injection (Fig.…”
Section: Type II Diabetes Increases Sglt-and Glut-mediated Transport supporting
confidence: 55%
“…The present study used animal models of diabetes and models of diet-induced obesity and insulin resistance of differing aetiology to assess the effects of insulin resistance and hyperglycaemia on expression of glucose transporters at the renal BBM. Our previous findings have shown that expression of GLUT2 and its regulator, PKC-βI, are increased in a model of established type I diabetes (Marks et al 2003) and that their expression levels are correlated with changes in glucose concentration within the pathophysiological range (Goestemeyer et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, STZ-diabetes can target GLUT2 protein (but not GLUT1) to the brush border membrane of proximal tubules (87). The latter may be linked to protein kinase C PKC␤1 activation (49,107,108) and implicates facilitative glucose transport in the increased glucose reabsorption across the apical membrane in the diabetic kidney (Fig. 1B).…”
Section: Hyperglycemia Enhances the Reabsorption Of Glucose In The Prmentioning
confidence: 99%
“…In the early S1 segment, where the bulk of filtered glucose is reabsorbed, the low affinity/ high capacity glucose transporters, SGLT2 and GLUT2 are co-expressed in the luminal brush border membrane and in the basolateral membrane, respectively. Increases in the cortical GLUT2 gene expression have been extensively reported in diabetes (9)(10)(11)(12)(13)(14)(15), and are important for renal glucose reabsorption maintenance in this condition, since high blood and interstitial glucose concentrations may lower the outwardly directed glucose gradient from tubule to blood (11). GLUT1 protein is also detected in the outer renal cortex, where it is not related to the tubule epithelial cells, but to the mesangial cells (16).…”
Section: Introductionmentioning
confidence: 99%